2001
DOI: 10.2500/105065801781543664
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral and Bilateral Effects of Nasal Septum Surgery Demonstrated with Acoustic Rhinometry, Rhinomanometry, and Subjective Assessment

Abstract: Little is known of what happens after an operative correction of nasal septum deviation in the cavity contralateral to the major septum deviation. We studied the effects of septoplasty on the objective and subjective unilateral and bilateral nasal airway in 117 consecutive patients presenting for septoplasty due to a clinically obstructing septum deviation. Significant median increases in nasal flow and cross-sectional areas were noted postoperatively on the deviation side, whereas on the contralateral side th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
69
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 12 publications
8
69
0
13
Order By: Relevance
“…Literatürdeki birçok çalışmada istatistiksel analizler, deviye tarafın verileri üzerinden ve nazal siklusun etkilerinden korunmak için dekonjesyon sonrası ölçümler kullanılarak yapılmıştır. [8][9][10][11][12][13][14][15][16] Çalışmamızda deviye tarafta hem dekonjesyon öncesi hem dekonjesyon sonrası, ameliyat sonrası MCA1, MCA2 değerleri ve hacim değerlerinde istatistiksel olarak anlamlı artış sağlandı ve bu sonucun literatürle uyumlu olduğu görüldü. [8][9][11][12][13][14][15][16] Truilhé ve Stoll [14] 102 hasta üzerinde yaptıkları çalışmada septoplasti sonrası dönemde MCA'da %26, hacimde %30 oranında artış saptanmıştır.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Literatürdeki birçok çalışmada istatistiksel analizler, deviye tarafın verileri üzerinden ve nazal siklusun etkilerinden korunmak için dekonjesyon sonrası ölçümler kullanılarak yapılmıştır. [8][9][10][11][12][13][14][15][16] Çalışmamızda deviye tarafta hem dekonjesyon öncesi hem dekonjesyon sonrası, ameliyat sonrası MCA1, MCA2 değerleri ve hacim değerlerinde istatistiksel olarak anlamlı artış sağlandı ve bu sonucun literatürle uyumlu olduğu görüldü. [8][9][11][12][13][14][15][16] Truilhé ve Stoll [14] 102 hasta üzerinde yaptıkları çalışmada septoplasti sonrası dönemde MCA'da %26, hacimde %30 oranında artış saptanmıştır.…”
Section: Discussionunclassified
“…[8][9][10][11][12][13][14][15][16] Çalışmamızda deviye tarafta hem dekonjesyon öncesi hem dekonjesyon sonrası, ameliyat sonrası MCA1, MCA2 değerleri ve hacim değerlerinde istatistiksel olarak anlamlı artış sağlandı ve bu sonucun literatürle uyumlu olduğu görüldü. [8][9][11][12][13][14][15][16] Truilhé ve Stoll [14] 102 hasta üzerinde yaptıkları çalışmada septoplasti sonrası dönemde MCA'da %26, hacimde %30 oranında artış saptanmıştır. Kemker ve ark.nın [15] 1999 yılın-da yayınladığı bir çalışmada ise nazal cerrahinin nazal kavite üzerindeki etkisi akustik rinometriyle değerlendirilerek ameliyat sonrası dönemde hastaların deviye nazal kavitelerinin hacim ve kesit alan değerlerinde belirgin artış olduğunu göster-mişlerdir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Previous studies have shown that either spreader grafts or lateral suspension technique alone may sometimes fail to improve nasal breathing in patients with dysfunctional nasal valves (17). Because most patients with nasal valve dysfunction actually have a combination of both narrow nasal valve angles together with weak upper lateral cartilages, tackling one side of the problem would not practically solve the breathing problem on a longterm basis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also shows that these technical limitations do not invalidate the clinical usefulness of this method for posterior regions of the nasal cavity. The method may be employed in comparisons in the same subject, such as when investigating relative volume variations caused by velar movement in silent speech, [30][31][32] or to analyze variations caused by surgery (tonsillectomies, 33,34 septoplasty/turbinectomy 1,35,36 , or maxillomandubilar osteotomy 37,38 ), taking into account that systematic errors are common, that random errors may be minimized, and that measurements are reproducible in the same subject. 29 …”
Section: Discussionmentioning
confidence: 99%